The missing link in the Chain of oppression and resistance: last era of Kurdish banditry in modern Turkey, 1950-1980 - Özcan, Ahmet. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2014., 2014)
Referring to the denomination of the transitory period between the massive Kurdish insurrections suppressed in the early Republic and the organized armed struggle initiated in the late 1970s as ‘the period of silence’, the present thesis demonstrates that the period between 1950 and 1980 had been active both in the sense of State oppression and Kurdish resistance against it through the analysis of criminality in the Kurdish regions from the 1950s onwards. While the linkage between Kurdish criminality and the ‘Eastern’ question had instantly been forged, the rise of ordinary crimes was reconstructed either as one of the natural results of the ‘underdevelopment of the Eastern regions’ or as the overt sign for an upcoming Kurdish rebellion. Despite such discursive variations, all the Governments from the 1950s onwards applied mainly the same policies and technologies of power (i.e. (i) disarmament of the population, organization of (ii) massive bandit hunts, and (iii) a series of commando raids) against a perceived rise of criminality in the Kurdish regions. Detecting ‘separatism’ behind the ordinary crimes, the State used the Kurdish criminality to veil its penetration into the region in pursuit of suppressing the Kurdish ethno-political identity. While the massive emergence of banditry in the Kurdish regions from the 1950s onwards had been a spontaneous reaction of the traditional Kurdish society against the socio-economic transformation of the region, the inversion of the ‘Western’ political and moral values through the ‘Eastern’ bandit myth constituted the ‘primitive’ form of resistance against the penetration of the Turkish nation-state building process into the region.
Keywords: Brigands and robbers -- Kurdish.; Brigands and robbers -- Political aspects -- Turkey.